Preparation and characterization of monoclonal antibodies against native membrane-bound penicillin-binding protein 1B of Escherichia coli. - Den Blaauwen, T (1989)
We prepared monoclonal antibodies against penicillin-binding protein 1B (PBP 1B) of Escherichia coli to study the membrane topology, spatial organization, and enzyme activities of this protein. The majority of the antibodies derived with PBP 1B as the immunogen reacted against the carboxy terminus. To obtain monoclonal antibodies recognizing other epitopes, we used PBP 1B lacking the immunodominant carboxy-terminal 65 amino acids as the immunogen. Eighteen monoclonal antibodies directed against membrane-bound PBP 1B were isolated and characterized. The epitopes recognized by those monoclonal antibodies were located with various truncated forms of PBP 1B. We could distinguish four different epitope areas located on different parts of the molecule. Interestingly, we could not isolate monoclonal antibodies against the amino terminus, although they were specifically selected for. This is attributed to its predicted extreme hydrophilicity and flexibility, which could make the amino terminus very sensitive to proteolytic degradation. All antibodies reacted against native PBP 1B in a dot-blot immunobinding assay. One monoclonal antibody also recognized PBP 1B in a completely sodium dodecyl sulfate-denatured form. This suggests that all the other monoclonal antibodies recognize conformational epitopes. These properties make the monoclonal antibodies suitable tools for further studies.